From initiation of convective storms to their impact — the Swabian MOSES 2023 campaign in southwestern Germany - Handwerker, Jan; Barthlott, Christian; Bauckholt, Matteo; Belleflamme, Alexandre; Böhmländer, Alexander; Borg, Erik; Dick, Galina; Dietrich, Peter; Fichtelmann, Bernd; Geppert, Gernot; Goergen, Klaus; Güntner, Andreas; et al. (Frontiers in Earth Science, 2025)
Since a comprehensive understanding of the water cycle cannot be developed by a single discipline alone, several institutes of the Helmholtz Association have joined forces to investigate extreme hydro-meteorological events in the framework of the 10-year “Modular Observation Solutions for Earth Systems” (MOSES) program. A key element of MOSES is conducting joint field experiments accompanied by coordinated modeling activities. A recent example is the “Swabian MOSES” campaign in southwestern Germany in 2021 involving several university institutes and the German Weather Service (DWD). In the summer of 2023, a second campaign, “Swabian MOSES 2023″ was conducted that extended and complemented the first one in several ways. The study area was enlarged to stretch from Mount Feldberg in the southern Black Forest to around Tübingen in the Neckar Valley. The former is known for the frequent initiation of thunderstorms, which then intensify and propagate northeastward, causing a hotspot for hail and heavy precipitation in the Neckar Valley. The “trigger area” around Feldberg was equipped with radars, Doppler wind lidars, radiosondes, a microwave radiometer, energy balance stations, meteorological towers, hail sensors, Global Navigation Satellite System (GNSS) stations, and optical disdrometers. The downstream “impact area”, in particular in the Lindach Valley, a small catchment near Tübingen, was equipped with two energy balance stations, a cosmic ray neutron sensing (CNRS) sensor, a gravimeter, hail sensors, and optical disdrometers for detailed studies of the hydrological impacts. A mobile CRNS device carried out measuring tours through the impact area, and a mobile storm-chasing team launched swarmsondes into several thunderstorms. These observational data are used to validate meteorological (ICON, ICOsahedral Non-hydrostatic) and hydrological (mHM, ParFlow) models. This paper describes the concept of the observation campaign and the accompanying modeling activities and shows some illustrative first results. In the future, we plan to assimilate the campaign observations into the high-resolution numerical model ICON to (i) bridge gaps between observations and (ii) assess the impact of additional observations on the model analysis and forecasts using targeted data denial experiments.